Determinants of Stock Returns: The Role of Financial Performance and Corporate Social Responsibility (E-Jurnal Akuntansi, 2026)
This study examines the effect of EPS, ROA, DER, and CSR on stock returns of companies listed in the LQ45 index during 2020–2024. Using a quantitative approach with panel data regression, 15 firms (75 observations) were selected through purposive sampling and analyzed using EViews 13. The results indicate that EPS and ROA have a positive and significant effect on stock returns, emphasizing the importance of profitability. DER shows no significant effect, suggesting leverage is not a key consideration for investors. Meanwhile, CSR has a negative and significant effect, implying it may be perceived as a cost reducing short-term gains. Collectively, all variables significantly influence stock returns, offering insights into investor behavior during the COVID-19 and post-pandemic period.
Keywords: Earnings Per Share; Return on Assets; Debt to Equity Ratio; Corporate Social Reponsibility; Stock Returns